EPP Energy Efficiency Calculation and Influencing Factor Analysis: Cases in China. (23rd August 2015) - Wang, Jingmin; Zhu, Yiping; Li, Yakun
Abstract : Efficiency power plant (EPP) promotes the use of energy efficiency power plant technology and energy efficient equipment, coupled with its low-input, zero pollution, zero emissions, and other advantages, having an important role in the control of energy consumption and energy saving. In order to carry out scientific EPP investment decisions, the level of energy efficiency is an important basis for investment decisions. This paper introduces total factor energy efficiency (TFEE) in energy efficiency calculation of EPP, constructs energy efficiency calculation model considering environmental benefits, and takes the micro and macro cases in China for analysis; the results show that the TFEE of both single energy efficiency project and EPP are at a relatively high level (above 0.7), and there is a huge gap between calculation results considering and without considering the environmental benefit. In order to discuss energy efficiency influencing factors, the paper analyzes generalized technological advances variation feature of China typical provinces implementing EPP based on generalized technological advances decomposition model by Malmquist index, finding that the steady growth ofM index in these provinces is derived from the management level of implementation of EPP and the large-scale production capacity of formation and management. We hope the models and conclusions could provide some references on EPP energy efficiency calculation and decision.